Pengembangan Instrumen Tes Berpikir Kritis Berbasis Sintesis Watson-Glaser dan Ennis - Tariza Fairuz; Nadia Mubarokah; Sri Masnita Pardosi; Shofia Lubis (Universitas Indraprasta PGRI, 2026)
The limitations of science assessment instruments that are able to measure critical thinking skills comprehensively, particularly in integrating cognitive dimensions and operational indicators into one complete construct, is still a problem in learning evaluation practices. This study aimed to develop a critical thinking test instrument based on the synthesis of the Watson–Glaser and Ennis frameworks in the context of science education. The research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The instrument was developed by synthesizing Watson–Glaser critical thinking components and Ennis’ operational indicators, which were then translated into multiple-choice reasoning-based items on wave and optics topics. Expert validation was conducted to evaluate content, construct, and language aspects. The instrument was tested on 38 undergraduate students of science education in Universitas Negeri Medan. The results indicated that the instrument was valid based on expert judgment and demonstrated adequate construct validity. Reliability analysis using Cronbach’s Alpha yielded a coefficient of 0.876, indicating high internal consistency. These findings suggest that the developed instrument reliably measures critical thinking skills in accordance with the synthesized Watson–Glaser and Ennis framework. The instrument can serve as an alternative assessment tool for science learning that emphasizes critical reasoning.